Meningkatkan berpikir kritis pada mahasiswa dengan pemanfaatan artificial intelegent pada pembelajaran pendidikan agama islam - Syarifuddin Syarifuddin (SAP (Susunan Artikel Pendidikan), 2025)
21st Century Learning requires students not only to master knowledge, but also to have critical thinking skills that are able to face the complexity of life's problems, including in understanding and internalizing Islamic values. In this context, the integration of artificial intelligence (AI) technology in the Islamic Religious Education (PAI) learning process offers new opportunities that can optimize students' intellectual potential. AI not only functions as a learning aid, but also as a thinking partner that is able to facilitate discussions, provide quick feedback, present a variety of religious perspectives, and present contextual simulations that challenge students to think deeply, analytically, and reflectively about religious teachings. Through this technology-based learning approach, students are encouraged not only to receive material passively, but to actively explore meaning, compare arguments, and build a more comprehensive understanding of Islamic values. The research was conducted through a qualitative approach with data collection techniques in the form of observation, in-depth interviews, and documentation studies at several universities that have adopted AI technology in their learning process. This research aims to explore how the strategic use of AI in the PAI learning process can improve students' critical thinking skills, as well as identify the most effective teaching models and strategies in integrating this technology.